Challenges and lessons from a primary care intervention in a Brazilian municipality - Mônica V Andrade; Kenya Noronha; Clareci S Cardoso; Claudia D L Oliveira; Júlia A Calazans; Michelle N Souza (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE To address the implementation of the Lab for Innovation in Chronic Conditions in Santo Antonio do Monte, indicating the main challenges and lessons of a new chronic condition model. METHODS This is an observational study based on two sources of data: 1) two cross-sectional household surveys, 2013 (2012 as reference year) and 2015 (2014 as reference year), representative for the entire population and four target groups (pregnant women; children under two years old; individuals with hypertension and diabetes); medical records of individuals who self-reported having hypertension or diabetes in the household survey of 2013. A descriptive statistics analysis was performed. RESULTS The main findings showed that the public health system is the main provider of health services, mainly primary care, in Santo Antonio do Monte. Besides, the implementation of Lab for Innovation in Chronic Conditions showed the importance of building a Primary Health Care network in small municipalities. CONCLUSIONS Community health agents and health managers played a fundamental role in the Primary Health Care network. The case study of Santo Antonio do Monte poses some challenges and lessons that clarify future interventions on building a Primary Health Care network that is essential to provide an adequate and longitudinal care to chronic conditions.